Mineral supplementation of feedlot cattle - Van Bibber-Krueger, Cadra (Kansas State University, 2016)
Four studies evaluated effects of mineral supplementation on feedlot performance, carcass characteristics and ruminal fermentation of finishing cattle. Study 1 supplemented 0 or 3.3 g/d yeast combined with Cr propionate to steers separated into light and heavy groups. No treatment x weight group interactions were observed for ADG, DMI, final BW, carcass traits, or plasma glucose of lactate concentrations (P ≥ 0.06). A treatment x weight group interaction was observed for G:F (P = 0.03). In study 2, steers were supplemented 60 or 300 mg Zn/kg DM with or without zilpaterol hydrochloride (ZH). No interactions or effects of Zn or ZH were observed for IGF-1, plasma glucose, or lactate concentrations (P > 0.05). Plasma urea nitrogen (PUN) concentration decreased with ZH (P < 0.01). No interactions or effects of Zn or ZH were detected for ADG, DMI, final BW, G:F, and carcass traits were minimally affected (P ≥ 0.05). Study 3 evaluated effects of supplementing 30 or 100 mg Zn/kg DM (30 or 100Zn) with and without ractopamine hydrochloride (RH; 200 mg/d). No interactions or effects of Zn were observed for feedlot performance or PUN (P ≥ 0.07). Final BW, ADG, and HCW increased when heifers were fed RH (P ≤ 0.02). Zinc x RH interactions were observed for LM area and yield grade (P ≤ 0.01), but other carcass traits were not affected (P ≥ 0.08). In study 4, heifers were supplemented 0, 30, 60, or 90 mg Zn/kg DM. Zinc supplementation did not affect final BW, ADG, or DMI (P ≥ 0.07), but G:F increased linearly (P = 0.02). Carcass traits were not affected by Zn supplementation (P ≥ 0.07). Effects of in vitro Zn titration (0, 30, 60, 60, 90, 120, or 150 mg/kg Zn) were evaluated using ground corn and soybean meal as substrate. In vitro fermentation was not affected by added Zn (P ≥ 0.05). These studies suggest Cr and Zn supplementation minimally affected carcass traits, but Zn supplementation up to 60 mg/kg improved feed efficiency with minimal impact on ruminal fermentation. Supplementing increased Zn concentrations may alter fat and muscle deposition when fed with RH.
Keywords: Zinc; Finishing cattle; Chromium propionate; Feedlot performance